CARBON MATERIALS FOR ELECTRONIC, ENVIRONMENTAL AND BIOMEDICAL APPLICATION - Kim, Seong-Cheol (PROSIDING SENATEK FAKULTAS TEKNIK UMP, 2015)
The carbon materials are the focal point of materials science especially in the field of environmental, biomedical and electrical materials. The focus of my presentation is the introduction of new carbon materials developed in last two decades. The materials include fullerenes, carbon nanotubes, and graphenes. The basic physical properties of the carbon nanomaterials will be introduced in the order of fullerene, nanotube and graphenes. Some of these properties are unique and superior to those of metals, polymers and ceramics. The properties of these materials make them useful for enhancing surface-to-volume ratio, reactivity, strength and durability. Some of the applications of these properties are included in the presentation.